Onderkomen - Vugt, van Jacqueline (The Netherlands, 2018)
The film tells the story of three illegal Afghan boys in Holland who are searching for their future and identity as homosexuals or Christian. They are supported by Dutch pensioners who help them to survive and to find their way through Dutch society, rules and regulations.
Verzio Film Festival Submission
Keywords: Documentary films